The Effect of Organizational Commitment and Work Motivation on Organizational Climate PT. Dodorindo Jaya Abadi Tanjung Morawa - Elcy Handayani Pramita; Aidil Putra (Jurnal Mantik, 2022)
PT. Dodorindo Jaya Abadi is: a company that has been accredited and established since 1997 by providing a variety of baby products branded Dodo which is ISO 9002 certified so that it has products of international quality. Even though PT. Dodorindo Jaya Abadi has expanded to almost all regions in Indonesia, but for a company headquartered in Tanjung Morawa – Medan, North Sumatra. Various complaints about the workplace or an uncomfortable working atmosphere for employees while working. The company cannot commit to its employees where the company cannot keep its promises even though the employees have worked with all their heart. Employees are not driven to give the best or the most optimal for the company. This research uses quantitative descriptive research. The total population in the study was 447 employees with the sampling technique using the Slovin formula, obtained as many as 82 samples. Simultaneously there is a significant influence between the variables of organizational commitment and work motivation on the organizational climate of employees of PT. Dodorindo Jaya Abadi. While partially found the variable organizational commitment has a significant effect on the organizational climate of employees of PT. Dodorindo Jaya Abadi. Partially, it was found that the work motivation variable had a significant effect on the organizational climate of the employees of PT. Dodorindo Jaya Abadi. The results of this study indicate that the variable of work motivation has more influence than organizational commitment on the organizational climate of employees of PT. Dodorindo Jaya Abadi.